The Metamorphosis of Social Movement in Banten: From Identity Romantism to Environment Agrarian Issues - Tarmiji Alkhudri, Ahma; H. Dharmawan, Arya; A. Kinseng, Rilus; Tjondronegoro, S.M.P (Sodality: Jurnal Sosiologi Pedesaan, 2018)
AbstractThis study aims to analyze the metamorphosis of social movements in Banten. In terms of methodology, this research uses a critical paradigm - a qualitative approach. In terms of methodology, this research uses a critical paradigm - a qualitative approach. The results show that there is a metamorphosis of social movements in Banten since the colonial era until the reform, both in terms of issues, actors, and ideology. First, the colonial era until the beginning of independence (1813-1945) issues of movement related to identity and political economy. The dominant actors of the movement are the nobles, the ulama, and the jawara, with the spirit of ideology of liberation from colonial rule (freedom and religous heavy). Second, the era of Orla-Orba (1945-1998) motive of the resistance movement around the issue of political economy (sentiment of ethnicity), agrarian, and education. The dominant actors in this era are: the people, the ulama, and the jawara. The characteristics of the movement are sporadic, partial, not systemic and not sustained by a strong ideology (pseudo populism haevy). Third, the reform era, the resistance movement questioned agrarian and environmental issues. The dominant actors are the people in the set of Local NGOs, (fishemen), ulama, and jawara. In this era, the rationalism and objectives of the resistance are clearer, coordinated, systemic, and based on the ideology of justice/populist (justice/polulism heavy).Keywords: metamorphosis, social movement, agrarian, enviroment, BantenAbstrakPenelitian ini bertujuan untuk menganalisis metamorfosis gerakan sosial di Banten. Dari sisi metodologi, penelitian ini menggunakan paradigma kritis – pendekatan kualitatif. Hasil penelitian menunjukkan bahwa terjadi metamorfosis gerakan sosial di Banten sejak era kolonial hingga reformasi, baik dari sisi isu, aktor, dan ideologi. Pertama, era kolonial hingga awal kemerdekaan (1813-1945) isu gerakan terkait dengan identitas dan ekonomi politik. Aktor gerakan yang dominan adalah kaum bangsawan, ulama, dan jawara, dengan semangat ideologi pembebasan dari penjajahan kolonial (freedom and religous heavy). Kedua, era Orla-Orba (1945-1998) motif gerakan perlawanan seputar isu ekonomi politik (sentimen etnisitas), agraria, dan pendidikan. Aktor yang berperan dominan pada era ini antara lain: rakyat, ulama, dan jawara. Ciri gerakannya sporadis, parsial, tidak sistemik dan tidak ditopang oleh ideologi yang kuat (pseudo populism haevy). Ketiga, era reformasi, gerakan perlawanan menyoal isu agraria dan lingkungan. Aktor yang dominan ialah rakyat dalam himpunan NGO Lokal (nelayan), ulama, dan jawara. Pada era ini rasionalisme dan tujuan perlawanan lebih jelas, terkoordinir, sistemik, dan bertumpu pada ideologi keadilan/ populis (justice/polulism heavy).Kata kunci: metamorfosis, gerakan sosial, agraria, lingkungan, Banten